Pengaruh Konsep Diri dan Disiplin Belajar terhadap Motivasi Belajar Peserta Didik di Sekolah Menengah Pertama Negeri 4 Palu Pada Mata Pelajaran Pendidikan Agama Islam - Fitri Rahayu (Paedagogia: Jurnal Pendidikan, 2019)
The purpose of this study is to find out the significant effect of self-concept on learning motivation of VII grade students in SMP Negeri 4 Palu on Islamic Religious Education subjects, (2) knowing the effect of learning discipline on learning motivation of VII grade students at SMP Negeri 4 Palu in the eyes of Islamic Religious Education subjects and (3) determine the effect of self-concept and learning discipline on learning motivation of grade VII students in SMP Negeri 4 Palu on Islamic Religious Education subjects.This study uses a quantitative approach. The population in this study were 220 class VII students of SMP Negeri 4 Palu. The sample was determined using proportional random sampling technique using a formula developed by Isaac and Michael, so that a sample of 135 students was obtained. Primary data were obtained using a questionnaire. Data analysis techniques include descriptive analysis, and regression tests using simple regression and multiple regression.The results showed that (1) There was a significant influence between self-concept on learning motivation of VII grade students in SMP Negeri 4 Palu on Islamic Religious Education subjects, with a significance level of 5%, the magnitude of the effect of self-concept variables on students' learning motivation was 0, 615 means having a high influence (2) There is a significant influence between learning discipline on learning motivation of VII grade students in SMP Negeri 4 Palu on Islamic Religious Education subjects, with a significance level of 5%, the magnitude of the effect of the discipline of learning variables on motivation student learning is 0, 565, (3) There is a significant influence between self-concept and learning discipline on learning motivation of grade VII students in SMP Negeri 4 Palu on Islamic Religious Education subjects, with a significance level of 5%, the high influence of concept variables self and discipline of learning towards learning motivation of VII grade students of SMP Nege ri 4 Palu in Islamic Religious Education subjects is 0, 615. The contribution of self-concept variables and learning discipline to learning motivation variables is R2 x 100% or 0, 6152 x 100% = 37.9%, the remaining 62.1% is determined by other variables outside of this study include the level of interest, talent, attention, parenting parents and others.